Multicultural Education through Constructivist Learning Strategies - Ahmad Saefudin; Ro'fah Ro'fah; Dyah Arum Sari (Jurnal Iqra' : Kajian Ilmu Pendidikan, 2021)
The Madrasa as Islamic educational institutions has a crucial role in promoting multicultural education values ​​so that students avoid prejudice, suspicion, and intolerance. The Akidah Akhlak Teachers at MI Masalikil Huda 2 have a unique way to promote these values, namely through constructivism-based learning strategies. With a qualitative approach relying on the interview, observation, and documentation techniques, the researchers try to answer two important questions; how the teacher's strategy in introducing students to the values ​​of multicultural education and what approaches they use in the learning process in the classroom. Finally, this research concludes that teachers instill the values ​​of democracy, tolerance, equality or equality, brotherhood or kinship, and the value of unity in learning Akidah Akhlak. There are four constructivism strategies in the delivery of multicultural education, namely cooperative learning, conceptual achievement, exemplary, habituation, and role-playing. They also rely on historical approaches, gender perspective approaches, and aesthetic approaches. Thus, the claim that the madrasa is inconsistent in delivering Islamic religious material with a multicultural perspective is refuted by the findings of this research. Keywords: Multicultural Education, Constructivism Learning Strategies, Cooperative Learning.